The Talaqqi Method: Its Effectiveness on Students’ Ability to Memorize the Qur’an - Fajrin, Dewi Fortuna; Syafe’i, Imam; Azizah, Nurul; Hasanah, Uswatun; Rahmatika, Zahra (Journal of Innovation and Research in Primary Education, 2025)
This study aimed to examine the effect of the Talaqqi learning model on students’ Qur’an memorisation ability in the Al-Qur’an Hadith subject. Employing a quantitative approach with a quasi-experimental method and a posttest-only control group design, the study involved a sample of 63 eleventh-grade students selected through simple random sampling. The experimental group received instruction using the Talaqqi method, while the control group was taught using the Wahdah method. Memorisation ability was assessed based on three indicators: fluency, tajwid accuracy, and clarity of recitation. The research instrument was a questionnaire comprising 12 items, of which 5 were validated, yielding a reliability score of 0.740. Data were analysed using an independent sample t-test. The results indicated that the Sig. (2-tailed) value was 0.082 > 0.05, and the t-value did not exceed the critical t-table value, leading to the acceptance of H₀. Thus, it can be concluded that there was no significant difference between the Talaqqi and Wahdah methods in enhancing students’ Qur’an memorisation ability. These findings suggest that while both methods are applicable, the Talaqqi model does not offer a statistically significant advantage over the Wahdah method. Educators may consider selecting between the two approaches based on contextual needs, teaching style, and student preferences.